Exendin-4 Modulates Diabetes Onset in Nonobese Diabetic Mice - Hadjiyanni, Irene (The Endocrine Society, 2008)
Activation of the glucagon-like peptide-1 receptor (GLP-1R) is associated with expansion of β-cell mass due to stimulation of cell proliferation and induction of antiapoptotic pathways coupled to β-cell survival. Although the GLP-1R agonist Exenatide (exendin-4) is currently being evaluated in subjects with type 1 diabetes, there is little information available about the efficacy of GLP-1R activation for prevention of experimental type 1 diabetes. We examined the consequences of exendin-4 (Ex-4) administration (100 ng once daily and 2 μg twice daily) on diabetes onset in nonobese diabetic mice beginning at either 4 or 9 wk of age prior to the onset of diabetes. Ex-4 treatment for 26 wk (2 μg twice daily) initiated at 4 wk of age delayed the onset of diabetes (P = 0.007). Ex-4-treated mice also exhibited a significant reduction in insulitis scores, enhanced β-cell mass, and improved glucose tolerance. Although GLP-1R mRNA transcripts were detected in spleen, thymus, and lymph nodes from nonobese diabetic mice, Ex-4 treatment was not associated with significant changes in the numbers of CD4+ or CD8+ T cells or B cells in the spleen. However, Ex-4 treatment resulted in an increase in the number of CD4+ and CD8+ T cells in the lymph nodes and a reduction in the numbers of CD4+CD25+Foxp3+ regulatory T cells in the thymus but not in lymph nodes. These findings demonstrate that sustained GLP-1R activation in the absence of concomitant immune intervention may be associated with modest but significant delay in diabetes onset in a murine model of type 1 diabetes.